2012
DOI: 10.1002/fam.2145
|View full text |Cite
|
Sign up to set email alerts
|

Novel intumescent flame retardants: synthesis and application in polycarbonate

Abstract: SUMMARY Novel phosphorus‐containing and nitrogen‐containing intumescent flame retardants, bis‐aminobenzyl spirocylic pentaerythritol bisphosphonate (BASPB) and arylene‐N,N′‐bis(2,2‐dimethyl‐1,3‐propanediol phosphoramidate) (ABDPP), were synthesized, and their structures were characterized with Fourier transform infrared spectroscopy and 1H and 31P nuclear magnetic resonance. The phosphorus compounds were used to impart flame retardancy to polycarbonate (PC). Combustion behaviors and thermal degradation propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…When the CEPPA addition is up to 6 wt %, the residue char reaches 4.07%, which is the highest value among all of the samples. The data are consistent with the results of the vertical burning and LOI tests, which can be explained by the idea that the phosphorus‐containing monomer firstly was dissociated into small molecules during combustion and then reacted with compounds containing CHO bonds and formed more stable compounds containing PO bonds such as phosphate . The more stable compounds can cover the samples to promote the char formation and then inhibit oxygen from the flaming zone.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…When the CEPPA addition is up to 6 wt %, the residue char reaches 4.07%, which is the highest value among all of the samples. The data are consistent with the results of the vertical burning and LOI tests, which can be explained by the idea that the phosphorus‐containing monomer firstly was dissociated into small molecules during combustion and then reacted with compounds containing CHO bonds and formed more stable compounds containing PO bonds such as phosphate . The more stable compounds can cover the samples to promote the char formation and then inhibit oxygen from the flaming zone.…”
Section: Resultssupporting
confidence: 86%
“…It can be seen that pure PA66 has absorption peaks at 3302.8, 1638.3, and 1536.5 cm −1 assigned to NH, CO stretching and the combined absorption of both δ N‐H and ν C‐N , respectively, and the absorption peaks at 2861.1 and 2938.6 cm −1 are ascribed to CH 2  stretching . For those FR‐PA66 samples, it is observed that new peaks at 1125.2 cm −1 and 1038.5 cm −1 correspond to PO stretching and PN stretching, respectively, suggesting that CEPPA monomer has been introduced to the main chain of copolymer, as expected.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study by Zhao and co-workers[270] two phosphorus-containing and nitrogen-containing intumescent flame retardants, bis-aminobenzyl spirocylic pentaerythritolbisphosphonate (BASPB) and arylene-N,N'-bis(2,2-dimethyl-1,3-propanediolphosphoramidate) (ABDPP), were synthesized and melt-blended with PC. Formulations containing 7wt.-% turned out to give a remarkable increase of PC LOI value (from 28.1 to 36.8 and 35.9% for PC, PC+7wt.-% BASPB and PC+7wt.-% ABDPP, respectively) enabled PC composites able to pass V0 UL94 classification.…”
mentioning
confidence: 99%
“…In the recent decades, intumescent flame retardants (IFRs) have been extensively studied in the field of flame retardancy of plastics. [9][10][11][12][13][14] The IFR system generally consists of three components, an acid source, for example, ammonium polyphosphate (APP) and melamine phosphates, a carbon source, such as pentaerythritol (PER) and starch, and a blowing agent, for example, melamine (MEL). There are some publications on the research of IFR in rubbers.…”
Section: Introductionmentioning
confidence: 99%